CONNECTION BETWEEN LANGUAGE AND CULTURE - Yakhshiboev, Mirjalol Dilshod ogli (Innovative Development in Educational Activities, 2023)
Language is not only a tool for the exchange of information, but also a symbolic system with the power to create and shape symbolic realities, such as values, perceptions, identities through discourse. Language can be viewed as a verbal expression of culture. It is used to maintain and convey culture and cultural ties.